Strategi Pengelolaan Administrasi dalam Meningkatkan Mutu Pendidikan di Sekolah Dasar Terpadu Muhammadiyah 36 Medan - Nurintan Maghfirah; Nur Rahma Bone; Zahroddar Zahroddar; Mursal Aziz (Lembag, 2024)
This research aims to determine the School Administration Management Strategy in Improving the Quality of Education in Muhammadiyah 36 Integrated Elementary School. The main problem is what the school administration management strategy is and the inhibiting and supporting factors in administrative management in improving the quality of education in Muhammadiyah 36 Medan Integrated Elementary School. The type of research used is qualitative, using observation, interviews and documentation instruments. The results of the research show that the School Administration Management Strategy for Improving the Quality of Education in the Muhammadiyah 36 integrated elementary school is planning regarding the goals to be achieved, organizing the division of tasks, mobilizing by motivating and communicating with administrators, supervising and evaluating the results of the administrator's work. Factors inhibiting the management of school administration at Muhammadiyah 36 Integrated Elementary School, namely the lack of ability of administrators, limited administrative staff which makes work results less than optimal and sometimes there is still a lack of discipline in working as well as supporting factors for managing school administration, namely the availability of facilities and infrastructure that support the administration process. , the availability of adequate facilities according to current needs, as well as maximizing the use of available facilities so that work can be made easier.